Pharyngeal mucosal closure in total laryngectomy: comparison between vertical and T-shaped closure - Montemayor Alatorre, Adolfo; Serna Vázquez, Ruth Patricia; Santos Santillana, Karla Marisol; Morales del Ángel, Josefina Alejandra; Córtes Ponce, José R.; Treviño González, José Luis (2024)
Objective: The objective of this study was to compare the outcomes vertical and T-shaped pharyngoplasty closure techniques after total laryngectomy (TL) and to evaluate the factors associated with the development of pharyngocutaneous fistula. Method: We performed a retrospective study that included patients with a histopathological diagnosis of laryngeal cancer that underwent TL between 2009 and 2021. Results: Fifty-seven patients were included in the study. A total of 14 patients underwent a vertical closure of the neopharynx (24.6%), while 43 patients underwent a T-shaped closure (74.4%). Pharyngocutaneous fistula was the most common complication, observed in 40.4% of cases (n = 23). No difference in the rate of complications was observed between groups, with the exception of tracheal dehiscence which was reduced in patients with T-shaped closure (n = 2, 4.7% vs. n = 5, 35.7%, p = 0.002). Diabetes mellitus was more frequently observed in patients with the development of pharyngocutaneous fistula (n = 7, 30.4% vs. n = 3, 8.8%, p = 0.03). Conclusions: Although complications were lower in the T-shaped closure group, we could not establish the superiority of either technique.